ALOKASI WAKTU KERJA PRODUKTIF IBU RUMAH TANGGA STUDI KASUS WANITA PEDAGANG SAYUR DI KECAMATAN BERMANI ULU RAYA KABUPATEN REJANG LEBONG (Allocation of Productive Working Time for Housewives Case Study of Female Vegetable Traders in Bermani Ulu Raya District, Rejang Lebong Regency) - UNTARI, DWI; MULYASARI, GITA; PRIYONO, BASUKI SIGIT; ANDANI, APRI; YULIARSO, MOHAMAD ZUKARNAIN (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2025)
This study aims to analyze the allocation of productive working time among housewives who work as vegetable traders and to identify the factors influencing it in Bermani Ulu Raya District, Rejang Lebong Regency. As a vegetable production center, the area offers significant opportunities for women to participate in informal economic activities, particularly trading. A census method was employed, involving 60 housewives, using both descriptive quantitative analysis and multiple linear regression. The findings indicate that the highest time allocation is for leisure (52.40%), followed by domestic (34.16%), productive (9.21%), and social activities (4.23%). Age and the presence of toddlers significantly influence the allocation of productive working time, while education level and distance to the market show no significant effect. The study highlights the dual roles of housewives as caretakers and income earners amid economic pressures. These findings offer valuable insights for designing policies to empower women and promote efficient time management in rural economic settings.